THEORY OF NON-STEADY-STATE ELECTRICAL CHARACTERISTICS OF METAL-INSULATOR-METAL STRUCTURES WITH SCHOTTKY BARRIERS AND UNIFORMLY DISTRIBUTED INTERFACE IMPURITY STATES - Gupta, H. M. (Elsevier B.V., 1995)
The metal-insulator (or amorphous semiconductor) blocking contact is still not well understood. In the present paper, we discuss the non steady state characteristics of Metal-lnsulator-Metal Structure with non-intimate blocking contacts (i.e. Metal-Oxide-Insulator-Metal Structure). We consider a uniform distribution (in energy) of impurity states in addition to impurity states at a single energy level within the depletion region. We discuss thermal as well as isothermal characteristics and present expressions for the temperature of maximum current (T-m) and a method to calculate the density of uniformly distributed impurity states. The variation of mobility with electrical field has also been considered. Finally we plot the theoretical curves under different conditions. The present results are closing into available experimental results.